Hydraulic Tomography for Estimating the Diffusivity of Heterogeneous Aquifers Based on Groundwater Response to Tidal Fluctuation in an Artificial Island in Taiwan - Jet-Chau Wen; Hong-Ru Lin; Tian-Chyi Jim Yeh; Yu-Li Wang; Keng-Li Lin; Shao-Yang Huang (Geofluids)
This study investigated the hydraulic properties of the heterogeneous aquifers of an artificial island (Yunlin Offshore Industrial Park) in Taiwan. The research was based on the groundwater level response affected by tidal fluctuation using the hydraulic tomography (HT) to analyze the hydraulic diffusivity (α). Specifically, the power spectrum ratio of groundwater and tidal fluctuations derived from the Gelhar solution was used to estimate α in homogeneous aquifers; this, however, could not be applied in the artificial island. Next, the spatial distribution of the groundwater level response affected by tidal fluctuation was analyzed and found to be irregular, proving the existence of hydrogeological heterogeneity in the artificial island. Furthermore, the results of the estimated α using the HT showed low error and high correlation, 0.41 m2/hr and 0.83, respectively, between the optimal estimated heterogeneous and reference α fields in the synthetic aquifer. Last, the HT was used in the real tested scenario. By comparing the predicted groundwater levels of the optimal estimated heterogeneous α field and the observed groundwater levels of the real aquifer, it was found that the correlation was higher than 0.99. Therefore, the HT can be used to obtain the optimal estimated heterogeneous α field in the artificial island.